ENHANCING PRIMARY SCHOOL READING COMPREHENSION THROUGH INTEGRATED DIGITAL TECHNOLOGY AND PHONICS INSTRUCTION - Nishonova Zuxra Voxidjon qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This paper explores the integration of digital technology and phonics instruction to enhance reading comprehension among primary school students. As educational technology becomes increasingly prevalent, combining traditional phonics methods with digital tools offers a promising approach to improving literacy outcomes. Phonics, which focuses on the relationship between sounds and letters, is essential for developing decoding skills. When integrated with interactive digital platforms, phonics instruction can become more engaging and effective, fostering a love for reading and improving comprehension skills. This paper discusses the benefits of this integrated approach, including personalized learning experiences, increased student engagement, and the development of critical reading skills. Keywords. Digital technology, phonics instruction, reading comprehension, primary education, literacy development, educational technology, interactive learning, student engagement.